Adhesive composition for fuel cell sealing member, fuel cell member, and method for manufacturing fuel cell member
Patent Information
- Application Number
- JP2023124066
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0024】 本開示の燃料電池シール部材用接着剤組成物によると、基材またはシール部材の表面に塗布された状態において接着剤組成物が識別しやすい。よって、目視や色検査機などにより、塗布状態の良否判定が容易になる。結果、塗りむら、塗り残しなどが生じにくくなり、シール部材の剥がれ、シール性の低下などを抑制することができる。また、特定の染料を比較的少量用いることで、接着性と識別性とを両立させることができる。本開示の燃料電池用部材は、接着不良が少なく、シール性に優れる。本開示の燃料電池用部材の製造方法は、判定工程において、塗布された接着剤組成物の色により、塗布状態の良否を判定する。これにより、接着剤組成物の塗りむら、塗り残しなどを回避することができる。
Smart Images

Figure 2025020586000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an adhesive composition for bonding a constituent member and a sealing member of a fuel cell, a fuel cell member manufactured using the adhesive composition, and a method for manufacturing a fuel cell member. [Background technology]
[0002] A fuel cell has a stack structure in which many cells are stacked. The cell stack is fastened by end plates arranged on both sides in the stacking direction. For example, a cell of a polymer electrolyte fuel cell has an electrode member including a membrane electrode assembly (MEA) and separators arranged to sandwich the electrode member. Rubber seal members are arranged around the electrode members and between adjacent separators to ensure sealing and insulation against reaction gases and refrigerants. In order to maintain high sealing properties in the operating environment of a fuel cell, a method of integrating a seal member and a mating member using an adhesive is effective. For example, Patent Document 1 describes a method of bonding a rubber gasket (seal member) and a separator, in which a silane coupling agent-based primer is applied to the surface of the rubber gasket, the primer-coated surface is brought into close contact with the separator, and the rubber gasket is heated in a state of being pressure-bonded and fixed. Patent Document 2 describes an adhesive that contains a copolymer oligomer-type silane coupling agent having a specific ratio of hydrophilic and hydrophobic functional groups as a main component as an adhesive for bonding a seal member and a separator. In Patent Document 2, an adhesive containing a silane coupling agent as a main component is applied to the surface of a separator and dried, and then a rubber composition is laminated thereon, crosslinked, and bonded. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-183198 A [Patent Document 2] International Publication No. 2022 / 208926 [Patent Document 3] JP 2018-59630 A Summary of the Invention [Problem to be solved by the invention]
[0004] Adhesives that contain silane coupling agents as their main component are almost colorless and transparent, and the coating film that forms on the surface of the substrate, such as a separator, is extremely thin. For this reason, it is difficult to tell by visual inspection whether the adhesive has been properly applied to the specified area. If there are areas where the adhesive is not evenly applied or not applied, the sealing material may peel off or the sealing performance may decrease.
[0005] As a method for judging the state of application of the adhesive, a method of coloring the coating film by blending a colorant into the adhesive is considered. However, since the colorant does not have adhesive properties, depending on the blending amount, the adhesive properties may decrease. Pigments are known as colorants, but since pigments do not dissolve in solvents, they tend to settle, making it difficult to form a homogeneous coating film. In addition, since pigment particles that do not have adhesive properties are dispersed in the formed adhesive layer, the sealing material may easily peel off, or stress may be concentrated near the pigment particles due to the compressive force in the lamination direction, which may cause cracks in the sealing material starting from the pigment particles.
[0006] In this regard, Patent Document 3 describes that the adhesive for bonding the annular metal core material and the elastomer member is colored with a dye. However, the adhesive described in Patent Document 3 is a general adhesive such as a phenol resin or epoxy resin used in bearing parts of automobiles and wind power generators, and does not use a silane coupling agent. It is also described that the dye can be either water-soluble or oil-soluble. In other words, Patent Document 3 does not assume the use of a silane coupling agent as an adhesive component, and does not consider the compatibility of the dye with the adhesive component.
[0007] For example, in an adhesive, if the compatibility between the adhesive component and the dye is poor, the dye may precipitate or become lumpy, making it difficult to form a homogeneous coating film. In this case, the sealing member may be easily peeled off, or may crack due to compression force in the stacking direction. In addition, in a fuel cell, high dimensional accuracy is required as well as thinning of the components, and the thickness of the adhesive layer interposed between the sealing member and the mating member is also extremely thin. In this way, an adhesive for bonding the components of a fuel cell and the sealing member must satisfy the required characteristics unique to the fuel cell, and therefore it is difficult to achieve both adhesion and distinguishability.
[0008] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its objective the provision of an adhesive composition for fuel cell sealing members that is capable of achieving both adhesion and identifiability, a fuel cell member manufactured using the adhesive composition, and a method for manufacturing a fuel cell member. [Means for solving the problem]
[0009] (1) In order to solve the above problems, the adhesive composition for a fuel cell sealing member disclosed herein is an adhesive composition for a fuel cell sealing member that bonds a thin-plate-like substrate, which is a constituent member of a fuel cell, to a sealing member made of a rubber composition, and is characterized in that it comprises: (A) an adhesive liquid having an adhesive component whose main component is a silane coupling agent, or whose main components are a silane coupling agent and an organic titanate compound, and a solvent; and (B) a dye that is compatible with the adhesive component and dissolves in the solvent, wherein the content of the dye is 3 parts by mass or more and 25 parts by mass or less when the non-volatile content of the adhesive composition is 100 parts by mass, and the adhesive composition is colored with the dye in a color different from the color of the substrate or the sealing member.
[0010] The adhesive composition for fuel cell sealing members of the present disclosure (hereinafter, sometimes simply referred to as "adhesive composition") is colored with a dye. When the substrate is a substrate, the adhesive composition is colored in a color different from the color of the substrate, and when the substrate is a sealing member, the adhesive composition is colored in a color different from the color of the sealing member. This makes it easier to identify the adhesive composition on the surface of the substrate, and makes it easier to judge the quality of the coating state by visual inspection or a color inspection device. As a result, uneven coating and areas left uncoated are less likely to occur, and peeling of the sealing member and deterioration of the sealing properties can be suppressed. In the present disclosure, "color" mainly refers to the hue of the three elements of color, and refers to shades such as red, blue, green, and yellow.
[0011] In the adhesive composition of the present disclosure, the dye is compatible with the adhesive component and dissolves in the solvent. This makes it difficult for the dye to precipitate and for lumps to form, and a homogeneous coating film can be formed. As a result, peeling of the sealing member and deterioration of the sealing property can be suppressed. The content of the dye is 3 parts by mass or more and 25 parts by mass or less, assuming that the non-volatile content of the adhesive composition is 100 parts by mass. Since the coloring power is exerted by a relatively small amount of dye, even if the dye does not have adhesive properties, the adhesive properties are not likely to decrease. In this way, the adhesive composition of the present disclosure can achieve both adhesiveness and distinguishability.
[0012] (2) In the above-mentioned (1), the adhesive composition for a fuel cell sealing member may be applied to the substrate or the sealing member in a thickness of 0.01 μm or more and 1 μm or less. This configuration is suitable for realizing thinning and high dimensional accuracy of components required for fuel cells.
[0013] (3) In any of the above configurations, the adhesive composition for a fuel cell sealing member may be applied to the substrate. According to this configuration, a flexible rubber sealing member (which may be an uncrosslinked rubber composition) is laminated on a thin substrate, so that displacement of the sealing member is suppressed, and dimensional accuracy and workability are improved.
[0014] (4) In the above configuration (3), the substrate may be a separator. With this configuration, the adhesive reliability between the separator and the seal member can be improved.
[0015] (5) In the above configuration (4), the separator may be silver-based, and the dye may be black-based or red-based. According to this configuration, a black-based or red-based adhesive composition is applied to a silver-based separator. This makes the presence of the adhesive composition more noticeable on the separator, and makes it easier to determine whether the application is good or bad.
[0016] (6) In any of the above configurations, the dye may be a xanthene dye or an azine dye. With this configuration, it is easy to select a dye that is compatible with the adhesive component, dissolves in the solvent, and can provide coloring in a relatively small amount.
[0017] (7) The fuel cell member of the present disclosure comprises a thin-plate substrate, a sealing member made from a rubber composition, and an adhesive layer that bonds the substrate and the sealing member, the adhesive layer being formed from the adhesive composition for fuel cell sealing members having the configuration described above in (1).
[0018] According to the fuel cell member of the present disclosure, the adhesive composition applied to the surface of the base material or sealing member during the manufacturing process is easy to identify, and the quality of the applied state can be easily determined by visual inspection, a color inspection device, etc. This makes it difficult for adhesion defects to occur, and realizes a high-quality fuel cell member with high sealing properties.
[0019] (8) In the above configuration (7), the thickness of the adhesive layer may be 0.01 μm or more and 1 μm or less. This configuration is suitable for achieving thin components and high dimensional accuracy required for fuel cells.
[0020] (9) In the configuration of (7) or (8) above, the substrate may be a separator made of stainless steel. This configuration can improve the adhesive reliability between the separator and the seal member. In addition, stainless steel separators usually have a silver-like color due to metallic luster. Therefore, when compared with the color of the separator, various colors such as black, red, blue, and green can be distinguished, which widens the range of dyes to be used for coloring.
[0021] (10) In any of the above (7) to (9), the rubber composition may comprise at least one rubber selected from the group consisting of ethylene-propylene rubber, ethylene-propylene-diene rubber, and ethylene-butene-diene rubber. This configuration makes it possible to realize a seal member having excellent sealing properties, durability, high-temperature properties, and the like.
[0022] (11) The manufacturing method of a fuel cell member of the present disclosure is a manufacturing method of a fuel cell member having the configuration of (7) above, characterized in that it comprises a coating step of coating the adhesive composition for a fuel cell sealing member onto the substrate, a judging step of judging whether the coating state is good or bad based on the color of the applied adhesive composition, and if the coating state is judged to be good, a bonding step of arranging the uncrosslinked rubber composition on the applied surface of the substrate to which the adhesive composition has been applied to form a laminate, heating and pressurizing the laminate to crosslink the rubber composition to form the sealing member, and bonding the sealing member to the substrate.
[0023] According to the manufacturing method of the fuel cell member of the present disclosure, in the judgment step, the quality of the coating state is judged based on the color of the applied adhesive composition. This makes it possible to avoid uneven coating, incomplete coating, etc. As a result, peeling of the sealing member, deterioration of the sealing property, etc. can be suppressed in the manufactured fuel cell member. Effect of the Invention
[0024] According to the adhesive composition for fuel cell sealing member of the present disclosure, the adhesive composition is easily identifiable when applied to the surface of a substrate or a sealing member. Therefore, it is easy to judge the quality of the applied state by visual inspection or a color inspection device. As a result, uneven application and leftover coating are less likely to occur, and peeling of the sealing member and deterioration of sealing properties can be suppressed. In addition, by using a relatively small amount of a specific dye, both adhesion and identifiability can be achieved. The fuel cell member of the present disclosure has few adhesion defects and is excellent in sealing properties. In the manufacturing method for a fuel cell member of the present disclosure, the quality of the applied state is judged by the color of the applied adhesive composition in the judgment step. This makes it possible to avoid uneven application and leftover coating of the adhesive composition. [Brief description of the drawings]
[0025] [Figure 1] 1 is a cross-sectional view showing one embodiment of a fuel cell member according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, the embodiments of the adhesive composition for a fuel cell sealing member, the fuel cell member, and the method for manufacturing the fuel cell member of the present disclosure will be described. Note that the embodiments are not limited to the following embodiments, and various modified and improved embodiments that can be implemented by those skilled in the art can be implemented.
[0027] <Adhesive composition for fuel cell seal members> The adhesive composition of the present disclosure bonds a thin-plate substrate, which is a component of a fuel cell, to a sealing member made of a rubber composition. Examples of fuel cells include polymer electrolyte fuel cells (PEFCs) (including direct methanol fuel cells (DMFCs)). Substrates vary depending on the type and configuration of the fuel cell, and examples of substrates in polymer electrolyte fuel cells include separators, membrane electrode assemblies (MEAs) that are electrode members, and gas diffusion layers (GDLs). The substrates and sealing members will be described later.
[0028] The adhesive composition of the present disclosure comprises (A) an adhesive liquid having an adhesive component whose main component is a silane coupling agent, or whose main components are a silane coupling agent and an organic titanate compound, and a solvent, and (B) a dye that is compatible with the adhesive component of the adhesive liquid and dissolves in the solvent.
[0029] (A) Adhesive liquid [Adhesive component] The main component of the adhesive component is a silane coupling agent or a silane coupling agent and an organic titanate compound. In this specification, the "main component" refers to a component that occupies 50% by mass or more when the entire adhesive component is 100% by mass. For example, the adhesive component may be in a form consisting of only a silane coupling agent (content ratio 100% by mass), in a form consisting of only a silane coupling agent and an organic titanate compound (content ratio of both together 100% by mass), or in a form containing a silane coupling agent, an organic titanate compound blended as necessary, and other components (content ratio less than 50% by mass).
[0030] The silane coupling agent may be appropriately selected from a group of compounds having one or more functional groups selected from an amino group, a vinyl group, and an epoxy group as a functional group, taking into consideration adhesiveness and the like. As the silane coupling agent, one type may be used alone, or two or more types may be mixed together. Alternatively, a copolymer oligomer in which two or more types of silane coupling agents are copolymerized may be used. As the copolymer oligomer, one having the following hydrophilic functional group (a) and hydrophobic functional group (b) is preferable. (a) One or more groups selected from the group consisting of a silanol group, an alkoxy group, an amino group, an isocyanate group, an epoxy group, a ureido group, a carboxy group, and a hydroxy group, and contains at least a silanol group or an alkoxy group. (b) one or more selected from the group consisting of a vinyl group, a (meth)acryloyl group, a maleimide group, a methyl group, an ethyl group, a styryl group, a phenyl group, and a mercapto group.
[0031] By making the hydrophilic functional group and the hydrophobic functional group in the silane coupling agent the specific functional groups shown in (a) and (b), the adhesive layer can be improved in adhesion, water resistance, and acid resistance. Among them, the hydrophobic functional group prevents water from penetrating into the adhesive layer by imparting hydrophobicity, and contributes to improving water resistance and acid resistance. The hydrophilic functional group reacts with the substrate or the components in the sealing member (carbon black, etc.) to contribute to adhesion. For example, a copolymerized oligomer may be produced by oligomerizing a silane coupling agent having the functional group of (a) and a silane coupling agent having the functional group of (b). In this specification, the (meth)acryloyl group means an acryloyl group or a methacryloyl group, and the (meth)acrylate means an acrylate or a methacrylate.
[0032] Among the silane coupling agents having a hydrophilic functional group (a), examples of the silane coupling agents having a hydrophilic functional group other than a silanol group and an alkoxy group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-isocyanatepropyltriethoxysilane, 3-ureidopropyltrialkoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-carboxypropyltrimethoxysilane, 3-carboxypropyltriethoxysilane, 3-hydroxypropyltrimethoxysilane, and 3-hydroxypropyltriethoxysilane. Of these, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane are preferred.
[0033] Examples of the silane coupling agent having a hydrophobic functional group (b) include vinyltrimethoxysilane, vinyltriethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, N-(trimethoxysilylpropyl)maleimide, N-(triethoxysilylpropyl)maleimide, p-styryltrimethoxysilane, p-styryltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, 3-mercaptopropylmethyltrimethoxysilane, 3-mercaptopropylmethyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, and n-propyltriethoxysilane. Among these, vinyltrimethoxysilane, vinyltriethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, N-(trimethoxysilylpropyl)maleimide, and N-(triethoxysilylpropyl)maleimide are preferred.
[0034] In the oligomerization reaction, first, each silane coupling agent is charged in a reactor having a distillation apparatus and a stirrer, and stirred at about 60°C for about 1 hour. Next, about 0.5 to 2.0 moles of an acid such as formic acid is added within 1 hour to a total of 1 mole of the silane coupling agent having a hydrophilic functional group shown in (a) and the silane coupling agent having a hydrophobic functional group shown in (b). While the acid is being added, the temperature in the reactor is maintained at about 65°C. The reaction is allowed to proceed by stirring for another 1 to 5 hours, and at the same time, the alcohol generated by hydrolysis is distilled under reduced pressure. When only water remains in the distillate, the distillation is stopped, and then the distillate is diluted so that the silane concentration is 30 to 80 mass%. The copolymerized oligomer obtained in this manner is an oligomer soluble in an alcohol-based organic solvent such as methanol or ethanol. The copolymerized oligomer is preferably a trimer or more from the viewpoint of improving the film-forming property, water resistance, and acid resistance when applying the adhesive composition.
[0035] Among the adhesive components, components other than the silane coupling agent include organic titanate compounds and aluminate coupling agents. When using one or more selected from organic titanate compounds and aluminate coupling agents, the total content ratio with the silane coupling agent may be 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or even 100% by mass. In addition, phenolic resins, bismaleimide resins, vinyl resins, etc. may be added for the purpose of improving the adhesion to the substrate and imparting hydrophobicity to improve the water resistance and acid resistance of the adhesive layer formed. When these resins are added, the amount is preferably 20% by mass or less when the total adhesive component is 100% by mass.
[0036] When an organic titanate compound is contained, the acid-resistant adhesion, particularly the acid-resistant adhesion during long-term use at high temperatures, is improved. As the organic titanate compound, it is preferable to use one or more compounds selected from titanium alkoxide, titanium chelate, and titanium acylate.
[0037] Examples of titanium alkoxides include tetramethyl titanate, tetraethyl titanate, tetra-normal propyl titanate, tetraisopropyl titanate, tetra-normal butyl titanate, tetraisobutyl titanate, tetra-t-butyl titanate, tetraoctyl titanate, tetrastearyl titanate, tetra(2-ethylhexyl) titanate, tetramethyl titanate, etc. Among these, tetraisopropyl titanate, tetra-normal butyl titanate, and tetrastearyl titanate are preferred.
[0038] Examples of titanium chelates include titanium acetylacetonate, titanium octylene glycolate, titanium tetraacetylacetonate, titanium ethylacetoacetate, titanium triethanolaluminate, etc. Among these, titanium acetylacetonate and titanium ethylacetoacetate are preferred.
[0039] Examples of titanium acylate include titanium isostearate, tri-n-butoxy titanium monostearate, di-i-propoxy titanium distearate, titanium stearate, di-i-propoxy titanium diisostearate, (2-n-butoxycarbonylbenzoyloxy)tributoxy titanium, etc. Among these, titanium stearate is preferred.
[0040] When an aluminate-based coupling agent is included, the coating strength is improved. Examples of the aluminate-based coupling agent include aluminum alkyl acetoacetate diisopropylate, aluminum ethyl acetoacetate diisopropylate, aluminum tris ethyl acetoacetate, aluminum isopropylate, aluminum diisopropylate mono secondary butylate, aluminum secondary butylate, aluminum ethylate, aluminum bis ethyl acetoacetate mono acetylacetonate, aluminum tris acetylacetonate, and aluminum monoisopropoxy mono oleoxy ethyl acetoacetate. These can be used alone or in combination of two or more. Among them, aluminum alkyl acetoacetate diisopropylate, aluminum ethyl acetoacetate diisopropylate, and aluminum tris ethyl acetoacetate are preferred.
[0041] [solvent] The solvent is not particularly limited as long as it can dissolve the adhesive component. Examples of the solvent include alcohol-based organic solvents such as methanol, ethanol, isopropanol, 2-ethoxyethanol (ethylene glycol monoethyl ether), and butoxyethanol (ethylene glycol monobutyl ether), and ketone-based organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone. The concentration of the adhesive component in the adhesive liquid may be appropriately determined in consideration of the adhesiveness, and may be, for example, 0.5% by mass or more and 25% by mass or less.
[0042] As the adhesive liquid having the copolymer oligomer of the silane coupling agent and the solvent, for example, commercially available products such as "CHEMLOK (registered trademark) 5151" manufactured by Lord Corporation, "MEGUM (registered trademark) 3290" manufactured by Dow Chemical Company, "X-12-1048" and "KR-513" manufactured by Shin-Etsu Chemical Co., Ltd. may be used.
[0043] (B) Dye The dye to be used is one that is compatible with the adhesive components of the adhesive liquid and dissolves in the solvent of the adhesive liquid. Here, "compatible with the adhesive components" means that when 1.5 g of the dye is added to 100 mL of adhesive liquid with a concentration of 5% by mass of the adhesive components and stirred for 5 minutes, the result is visually observed to be free of turbidity and precipitate.
[0044] The adhesive composition of the present disclosure is colored by a dye in a color different from the color of the substrate or the sealing member. When the adhesive composition is applied to a substrate, it is sufficient to color it in a color different from the color of the substrate, and when the adhesive composition is applied to a sealing member, it is sufficient to color it in a color different from the color of the sealing member. By making the color of the coating film different from the color of the substrate, rather than being colorless and transparent, it becomes easier to judge the quality of the coating state. The color of the dye is not limited, but it is preferable to use a color that stands out against the color of the substrate. For example, when the substrate is a silver-colored separator, it is preferable to use a black-colored or red-colored dye, since the presence of the adhesive composition applied to the substrate can be easily identified.
[0045] From the viewpoint of increasing the color as dark as possible to enhance the distinguishability, the content of the dye is 3 parts by mass or more when the nonvolatile content of the adhesive composition is 100 parts by mass. 5 parts by mass or more, and more preferably 10 parts by mass or more. On the other hand, from the viewpoint of ensuring the desired adhesiveness, the content of the dye is 25 parts by mass or less when the nonvolatile content of the adhesive composition is 100 parts by mass. 20 parts by mass or less, and more preferably 15 parts by mass or less. In this specification, "nonvolatile content" means the mass of the remaining components after removing the solvent from the adhesive composition. In addition, it is desirable to be able to distinguish the presence of the adhesive composition even if the coating film is thin. For example, even if the thickness of the coating film of the adhesive composition is 0.01 μm or more and 1 μm or less, it is preferable that the coloring power of the dye is exerted and the presence of the adhesive composition can be distinguished.
[0046] Xanthene dyes and azine dyes are suitable as dyes that have high coloring power even in relatively small amounts. Among xanthene dyes, rhodamines are preferable. Red dyes include rhodamine B (CI Basic Violet 10), CI Solvent RED 49, and CI Basic RED 1:1, while black dyes include CI Solvent Black 7. "CI" stands for Colour Index. The Colour Index is a database of colour materials compiled by the British Society of Dyes and Colourants and others.
[0047] <Fuel cell components> The fuel cell member of the present disclosure comprises a thin plate-shaped substrate, a sealing member made from a rubber composition, and an adhesive layer that bonds the substrate and the sealing member, the adhesive layer being formed from the adhesive composition for a fuel cell sealing member of the present disclosure.
[0048] First, an embodiment of the fuel cell member of the present disclosure will be described. FIG. 1 shows a cross-sectional view of the fuel cell member of this embodiment. As shown in FIG. 1, the fuel cell member 1 includes a separator 10, a seal member 20, and an adhesive layer 30. The separator 10 is made of stainless steel and has a rectangular thin plate shape with a silver-based color. A total of six grooves 11 extending in the longitudinal direction are recessed in the area of the separator 10 that overlaps with an electrode member (not shown) when a fuel cell is constructed. The grooves 11 become flow paths for a refrigerant, etc. The seal member 20 is disposed on the periphery of the upper surface of the separator 10. The seal member 20 has a frame shape when viewed from above. The seal member 20 is made of a cross-linked product of a rubber composition containing ethylene-butene-diene rubber. The seal member 20 has a lip portion 21 that protrudes upward. The top of the lip portion 21 has a curved surface shape. The seal member 20 elastically contacts another separator to be stacked when a fuel cell is constructed. The adhesive layer 30 has a frame shape when viewed from above, and is disposed between the separator 10 and the seal member 20. The adhesive layer 30 is formed from the adhesive composition of the present disclosure, and has a reddish color. The adhesive layer 30 bonds the separator 10 and the seal member.
[0049] The fuel cell member 1 is manufactured as follows. First, a rubber composition for forming the seal member 20 is prepared. The prepared rubber composition is molded into a predetermined shape to prepare an uncrosslinked rubber member. Next, the adhesive composition is applied to a predetermined position on the upper surface of the separator 10, and the application state is confirmed. Here, since the adhesive composition exhibits a reddish color, it is easy to identify on the upper surface of the silvery colored separator 10. Then, if the application state is good, the prepared rubber member is laminated on the upper surface of the coating film, and crosslinked and bonded under predetermined conditions. In this way, the fuel cell member 1 in which the separator 10 and the seal member 20 are integrated via the adhesive layer 30 is manufactured. Next, the individual members constituting the fuel cell member of the present disclosure will be described.
[0050] [Base material] As described above, the substrate used in the fuel cell varies depending on the type and configuration of the fuel cell, and in the case of a solid polymer electrolyte fuel cell, the substrate may be a separator, a membrane electrode assembly of an electrode member, a gas diffusion layer, etc. Among these, the material of the separator may be stainless steel, titanium, copper, magnesium, aluminum, carbon, graphite, conductive resin (thermoplastic resin or thermosetting resin including carbon, graphite, polyacrylonitrile carbon fiber, etc.), etc. From the viewpoint of acid resistance and cost, stainless steel (particularly austenitic) and titanium (particularly pure titanium) are preferable. In addition, a carbon thin film such as a diamond-like carbon film (DLC film) or a graphite film may be formed on the surface of the main body made of these materials by a process such as physical vapor deposition (PVD) or chemical vapor deposition (CVD). In order to increase the wettability of the adhesive composition and improve the adhesiveness, a surface treatment such as forming unevenness may be performed on the region of the separator where the seal member is adhered (the region where the adhesive composition is applied). The configuration of the separator, including the flow path and manifold hole to be formed, is not limited, and the shape, thickness, etc. may be appropriately determined. Considering power generation performance, the thickness of the separator is preferably 0.1 mm or more and 0.5 mm or less.
[0051] [Sealing material] The seal member is manufactured by subjecting the rubber composition to injection molding, press molding, or the like. The rubber component constituting the rubber composition may be liquid rubber or solid rubber. Examples of the rubber component include ethylene-propylene rubber (EPM), ethylene-propylene-diene rubber (EPDM), ethylene-butene-diene rubber (EBT), silicone rubber, fluororubber, butyl rubber (IIR), ethylene-propylene rubber (EPM), acrylonitrile-butadiene rubber (NBR), hydrogenated acrylonitrile-butadiene rubber (H-NBR), styrene-butadiene rubber (SBR), butadiene rubber (BR), and the like. Among them, it is desirable to use one or more selected from EPM, EPDM, and EBT because of their high water resistance and acid resistance at high temperatures. The rubber composition may contain a crosslinking agent, a crosslinking assistant, a plasticizer, a reinforcing agent, an antiaging agent, a processing assistant, and the like in addition to the rubber component.
[0052] As the crosslinking agent, it is desirable to use an organic peroxide because it does not contain volatile components such as sulfur. Among them, dialkyl peroxide, peroxyketal, peroxyester, ketone peroxide, diacyl peroxide, peroxydicarbonate, etc., which can be crosslinked at a relatively low temperature, are suitable. As the crosslinking assistant, maleimide compound, triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethylolpropane trimethacrylate (TMPT), bifunctional (meth)acrylate, 1,2-polybutadiene, etc. are listed. As the plasticizer, petroleum-based plasticizers such as process oil, lubricating oil, paraffin, liquid paraffin, and Vaseline, fatty oil-based plasticizers such as castor oil, linseed oil, rapeseed oil, and coconut oil, waxes such as tall oil, sab, beeswax, carnauba wax, and lanolin, linoleic acid, palmitic acid, stearic acid, and lauric acid are listed. As the reinforcing agent, carbon black, amorphous silica (white carbon), etc. are listed. Examples of the antioxidant include phenol-based, amine-based, imidazole-based, phosphoric acid-based, and wax-based antioxidants.
[0053] The sealing member may be disposed in a ring shape along the outer periphery on the surface of the base material, or may be disposed so as to surround a predetermined portion. The thickness of the sealing member is preferably 0.2 mm to 5 mm, more preferably 0.5 mm to 3 mm.
[0054] [Adhesive layer] The adhesive layer that bonds the substrate and the seal member is formed from the adhesive composition for fuel cell seal member of the present disclosure. From the viewpoint of realizing a thin component and high dimensional accuracy, the thickness of the adhesive layer is desirably 0.01 μm or more and 1 μm or less. The color of the adhesive layer is not particularly limited as long as it is different from the color of the member (substrate or seal member) to which the adhesive composition is applied.
[0055] <Method of manufacturing fuel cell components> One embodiment of the method for producing a fuel cell member according to the present disclosure includes a coating step, a determining step, and a bonding step. Each step will be described below in order.
[0056] [Coating process] In this step, the adhesive composition for fuel cell sealing members of the present disclosure is applied to a substrate. The adhesive composition may be prepared by preparing a dye solution in advance by dissolving a dye in a solvent, and mixing the dye solution and the adhesive solution. Alternatively, the adhesive composition may be prepared by adding a dye to the adhesive solution and stirring. The adhesive composition may be applied by brush coating, or by a coating machine such as a dispenser, blade coater, bar coater, die coater, comma coater (registered trademark), or roll coater, or by a spray method or immersion method, and then naturally dried at room temperature or dried by heating if necessary. The adhesive composition may be applied in two or more layers, but a single layer is preferable from the viewpoint of shortening the application process.
[0057] [Judgment process] In this step, the quality of the coating state is judged based on the color of the applied adhesive composition (coating film). The judgment may be made visually, with a color inspection machine, or both.
[0058] [Adhesion process] In this step, if the adhesive composition is judged to be applied in a good state, an uncrosslinked rubber composition is placed on the adhesive composition-applied surface of the substrate to form a laminate, and the laminate is heated and pressurized to crosslink the rubber composition to form a sealing member, and the sealing member is adhered to the substrate. In this step or before this step, a rubber composition for forming a sealing member is first prepared. The rubber composition may be prepared by kneading the rubber component and the components to be mixed as necessary with a roll, a kneader, a Banbury mixer, or the like. The prepared rubber composition may be molded into a predetermined shape by injection molding, press molding, or the like (preparation of an uncrosslinked rubber member). This eliminates the need for complicated positioning, facilitates continuous processing, and improves productivity. Then, a rubber composition (rubber member) is laminated on the coating film formed on the substrate, and heated and pressurized. Heating and pressurization may be performed using a press machine, a bonding machine, or the like. The heating temperature may be 130°C or higher and 200°C or lower, taking into consideration the crosslinking temperature of the rubber component, etc. The pressure to be applied may be appropriately set taking into consideration the adhesiveness and prevention of destruction of the sealing member, etc. The heating and pressurizing time (adhesion time) may be about 3 to 30 minutes.
[0059] The above describes a form in which an uncrosslinked rubber composition is used for crosslinking and bonding in the bonding process. However, the fuel cell components of the present disclosure may also be produced by a method in which a sealing member is produced in advance by crosslinking the rubber composition, and the sealing member is then placed on the surface of the substrate to which the adhesive composition has been applied, and heated and pressed as necessary. EXAMPLES
[0060] Next, the present disclosure will be described in more detail with reference to examples. Various adhesive compositions were prepared, and their discriminability when applied to a substrate was evaluated. In addition, the prepared adhesive compositions were used to adhere a sealing member to a substrate to prepare an evaluation sample, and the adhesiveness and compression durability of the sealing member were evaluated.
[0061] <Identification of adhesive composition> [Adhesive liquid (A1)] Two types of silane coupling agents were copolymerized to produce a copolymerized oligomer. First, 100 parts by mass of vinyltrimethoxysilane, 68.4 parts by mass of 3-aminopropyltrimethoxysilane, and 33.1 parts by mass of water were charged into a reactor having a distillation apparatus and a stirrer, and stirred at about 60°C for about 1 hour. Next, formic acid was added within 1 hour so that the amount added was 1.0 mole per mole of the total mass of the silane coupling agent. While adding formic acid, the temperature inside the reactor was maintained at about 65°C. The mixture was stirred for another 3 hours to proceed with the reaction, and at the same time, the alcohol produced by hydrolysis was distilled under reduced pressure. The distillation was stopped when only water was present in the distillate, and then the mixture was diluted so that the silane concentration was 50% by mass to obtain a copolymerized oligomer. The hydrophobic functional group in the copolymerized oligomer was a vinyl group, and the hydrophilic functional groups were a silanol group, an alkoxy group, and an amino group. The produced copolymer oligomer was diluted with a mixed solvent of methanol and ethanol (mass ratio 1:1) to obtain an adhesive liquid (A1) having a concentration of the copolymer oligomer (silane coupling agent) as the adhesive component of 5 mass %.
[0062] [Adhesive liquid (A2)] The adhesive component was prepared by mixing 12.5 parts by mass of tetraisopropyl titanate, an organic titanate compound, with 100 parts by mass of the copolymer oligomer (silane coupling agent) used in the adhesive liquid (A1). This was diluted with a mixed solvent of ethanol and 2-ethoxyethanol (mass ratio 9:1) to obtain an adhesive liquid (A2) with a concentration of the adhesive component of 5% by mass.
[0063] [Adhesive liquid (A3)] The adhesive component was prepared by mixing 100 parts by mass of the copolymer oligomer (silane coupling agent) used in the adhesive liquid (A1) with 50 parts by mass of the organic titanate compound tetraisopropyl titanate. This was diluted with a mixed solvent of ethanol and 2-ethoxyethanol (mass ratio 9:1) to obtain an adhesive liquid (A3) with a concentration of the adhesive component of 5% by mass.
[0064] Furthermore, commercially available adhesives containing a copolymer oligomer type silane coupling agent were prepared as adhesive liquids (A4) to (A6).
[0065] [Adhesive liquid (A4)] "CHEMLOK(R) 5151" manufactured by Lord Corporation. The hydrophilic functional groups of the copolymer oligomer are silanol groups and alkoxy groups, and the hydrophobic functional groups are vinyl groups. The solvent (diluent) is ethanol.
[0066] [Adhesive liquid (A5)] "MEGUM(R) 3290" manufactured by Dow Chemical Company. The hydrophilic functional groups of the copolymer oligomer are silanol groups, alkoxy groups, and amino groups, and the hydrophobic functional group is a vinyl group. The solvent is ethanol.
[0067] [Adhesive liquid (A6)] "KR-513" manufactured by Shin-Etsu Chemical Co., Ltd. The hydrophilic functional groups of the copolymer oligomer are silanol groups and alkoxy groups, and the hydrophobic functional groups are acryloyl groups and methyl groups. The solvent is ethanol.
[0068] [Coloring agent] Five types of dyes and one type of pigment were prepared as colorants. The details are as follows: (i) Dye (B1) Rhodamine B (CI Basic Violet 10), red. (B2)CI Solvent RED 49, red. (B3)CI Basic RED 1:1, red. (B4)CI Solvent Black 7, black. (B5) CI Acid Red 27, red. (ii) Pigments Carbon black: "Aqua-Black (registered trademark) 001" manufactured by Tokai Carbon Co., Ltd., black color.
[0069] [Production of adhesive composition] A colorant was added to a solvent and stirred to prepare a colorant liquid, and the colorant liquid was mixed with an adhesive liquid and stirred to prepare various adhesive compositions. The solvent added to the colorant was the same as that of the adhesive liquid to be combined. The adhesive compositions prepared were numbered from 1 to 15. Tables 1 and 2 show the components of the adhesive compositions (combinations of adhesive components and colorants in the adhesive liquid, and the contents of each). In Tables 1 and 2, the units of components are parts by mass when the non-volatile content of the adhesive composition is 100 parts by mass.
[0070] [Table 1]
[0071] [Table 2]
[0072] [Solubility of colorants in solvents] The colorant was added to the solvent of the adhesive liquid to be combined when producing the adhesive composition, and stirred, and visually observed to see whether it dissolved or not. As a result, all of the dyes used in the adhesive compositions No. 1 to 14 were dissolved (shown by ○ in Tables 1 and 2), but the pigment used in the adhesive composition No. 15 was not dissolved (shown by × in Table 2).
[0073] [Compatibility of colorants with adhesive components] 1.5 g of the colorant was added to 100 mL of an adhesive liquid with a concentration of 5% by mass of adhesive components, which is combined when producing an adhesive composition, and the state was visually observed after stirring for 5 minutes. The concentration of the adhesive components in the adhesive liquids (A4) to (A6) using commercially available adhesives was adjusted to 5% by mass using an appropriate solvent. The compatibility was evaluated as good when there was no turbidity or precipitate, and as poor when at least one of turbidity and precipitate was observed. As a result, the compatibility of the dyes used in the adhesive compositions No. 1 to 13 was good (shown by ○ in Tables 1 and 2), but the compatibility of the dye used in the adhesive composition No. 14 and the pigment used in the adhesive composition No. 15 was poor (shown by × in Table 2).
[0074] [Evaluation of distinctiveness] The adhesive composition thus produced was spray-coated on the surface of the substrate to a predetermined thickness, and after natural drying at room temperature (20°C ± 5°C), the coating film was visually observed. As the substrate, a silver-colored stainless steel plate made of SUS304 and a silver-colored titanium plate made of pure titanium were used. Both substrates were rectangular plates with a width of 25 mm, a length of 60 mm, and a thickness of 1.5 mm. The adhesive composition was applied to a square area with a width of 25 mm and a length of 25 mm on the surface of the substrate. The types of substrates and the thickness of the coating film (adhesive layer) are summarized in Tables 1 and 2 above. In Tables 1 and 2, the stainless steel plate is indicated as "SUS" and the titanium plate is indicated as "Ti".
[0075] As a result, for adhesive compositions No. 1 to 13 and 15, the color of the coating film was different from the color of the substrate regardless of the thickness of the coating film, and the coating film could be distinguished on the substrate (shown by ◯ in Tables 1 and 2). However, in sample No. 13, the dye content exceeded 25 parts by mass. Therefore, although the distinguishability was exhibited, the adhesiveness was reduced as described below. On the other hand, for adhesive composition No. 14, even if the coating film was 0.2 μm thick, the color was faint, and it was difficult to distinguish the coating film on the substrate (shown by × in Table 2). This is thought to be due to poor compatibility of the dye with the adhesive components. In addition, for adhesive composition No. 15, which uses a black pigment, the coating film could be distinguished on the substrate.
[0076] <Adhesion of Adhesive Composition and Compression Durability of Sealing Member> [Production of evaluation samples] First, a rubber composition for forming a seal member was prepared as follows. 100 parts by mass of ethylene-butene-diene rubber (Mitsui Chemicals, Inc., "EBT-K-9330M") as a rubber component, 1.0 part by mass of a phenolic antioxidant (Ouchi Shinko Chemical Industry Co., Ltd., "Nocrac (registered trademark) NS-5"), 50 parts by mass of carbon black (Tokai Carbon Co., Ltd., "Seat (registered trademark) SO") as a reinforcing agent, and 15 parts by mass of poly-α-olefin (Nippon Steel Chemical & Material Co., Ltd., "PAO601") as a plasticizer were kneaded for 5 minutes at 120 ° C. using a Banbury mixer. Then, the kneaded product was cooled, and 6 parts by mass of 1,1-di(t-butylperoxy)cyclohexane (NOF Corp., "Perhexa (registered trademark) C-80") as a crosslinking agent was added, and the mixture was kneaded for 10 minutes at 50 ° C. using an open roll to prepare a rubber composition.
[0077] Next, the rubber composition was placed on the surface of the substrate used in the evaluation of the discriminability so as to overlap the coating film of the adhesive composition to form a laminate, and this laminate was placed in a mold and heated and pressed at 170°C for 10 minutes. In this way, an evaluation sample was produced in which a sealing member (thickness 2.0 mm) which is a crosslinked product of the rubber composition and a substrate were bonded via an adhesive layer. Hereinafter, the number of the evaluation sample corresponds to the number of the adhesive composition used.
[0078] [Adhesion evaluation] A peel test was performed on the evaluation sample to evaluate the adhesion between the substrate and the seal member. In the peel test, a notch was made in the end of the seal member that was not adhered to the substrate to prepare a gripping part, and the gripping part was pulled in a direction perpendicular to the substrate at a speed of 10 mm / sec to peel off the seal member. The state of the peeled surface was then visually observed, and the adhesiveness was evaluated as good when the material broke (the seal member was cut) and as poor when the interface broke.
[0079] The peeling test was carried out on two types of samples, "initial" and "after immersion in acidic water". The "initial" sample was left at room temperature after production, while the "after immersion in acidic water" sample was produced by immersing the sample in a 90°C aqueous sulfuric acid solution (pH 3.0) for 368 hours, then removing it and leaving it at room temperature. The test results for the sample after immersion in acidic water are an index for judging the quality of acid-resistant adhesion at high temperatures.
[0080] As a result, the adhesiveness of samples No. 1 to 12 was good both initially and after immersion in acidic water (shown by a circle in Table 1 above). In contrast, the initial adhesiveness of sample No. 13, which had a high dye content, was poor (shown by a cross in Table 2 above). Since the initial adhesiveness of sample No. 13 was poor, the acid resistance adhesiveness was not evaluated. In addition, the adhesive properties of samples No. 14 and 15 were not evaluated because the compatibility of the colorant with the adhesive component was poor and the colorant precipitated in the adhesive composition.
[0081] [Evaluation of compression durability] A compression test was performed on the evaluation sample to evaluate the durability of the sealing member. The compression test was performed as follows. First, the evaluation sample was placed in a press machine and fixed in a state where the sealing member was compressed by 40% in the thickness direction. In this state, the temperature was raised to 100°C and held for 10 minutes. After that, it was cooled to room temperature and the evaluation sample was removed from the press machine. The removed sealing member of the evaluation sample was cut in the thickness direction and the cross section was visually observed. Then, if there was no crack, it was evaluated as having good compression durability, and if there was a crack, it was evaluated as having poor compression durability.
[0082] As a result, for samples No. 1 to 13, none of them had any cracks and the compression durability was good (shown by ○ marks in Tables 1 and 2 above). On the other hand, for samples No. 14 and 15, which used colorants with poor compatibility with the adhesive components, cracks occurred and the compression durability was poor (shown by × marks in Table 2 above).
[0083] From the above, it was confirmed that the adhesive compositions Nos. 1 to 12 could provide distinguishability while ensuring adhesion, and could easily determine whether the application state was good or bad. [Explanation of symbols]
[0084] 1: fuel cell member, 10: separator, 11: groove portion, 20: sealing member, 21: lip portion, 30: adhesive layer.
Claims
1. An adhesive composition for a fuel cell sealing member that bonds a thin-plate-like substrate, which is a component of a fuel cell, to a sealing member made of a rubber composition, comprising: (A) an adhesive liquid having an adhesive component whose main component is a silane coupling agent or whose main components are a silane coupling agent and an organic titanate compound, and a solvent; (B) a dye that is compatible with the adhesive component and soluble in the solvent; having the content of the dye is 3 parts by mass or more and 25 parts by mass or less, based on 100 parts by mass of the nonvolatile content of the adhesive composition; The adhesive composition for a fuel cell sealing member is characterized in that the adhesive composition is colored with the dye in a color different from the color of the base material or the sealing member.
2. The adhesive composition for a fuel cell sealing member according to claim 1 , which is applied to the substrate or the sealing member in a thickness of 0.01 μm or more and 1 μm or less.
3. The adhesive composition for a fuel cell sealing member according to claim 1 , which is applied to the substrate.
4. The adhesive composition for a fuel cell sealing member according to claim 3 , wherein the substrate is a separator.
5. the separator is silver-based in color; 5. The adhesive composition for a fuel cell sealing member according to claim 4, wherein the dye is black or red.
6. 2. The adhesive composition for a fuel cell sealing member according to claim 1, wherein the dye is a xanthene dye or an azine dye.
7. The present invention relates to a sealing member that is made of a rubber composition and has a thin plate-like base material, and an adhesive layer that bonds the base material and the sealing member, A fuel cell member, wherein the adhesive layer is formed from the adhesive composition for a fuel cell sealing member according to claim 1 .
8. 8. The fuel cell member according to claim 7, wherein the adhesive layer has a thickness of 0.01 μm or more and 1 μm or less.
9. 8. The fuel cell member according to claim 7, wherein the substrate is a separator made of stainless steel.
10. 8. The fuel cell member according to claim 7, wherein the rubber composition comprises at least one rubber selected from the group consisting of ethylene-propylene rubber, ethylene-propylene-diene rubber, and ethylene-butene-diene rubber.
11. A method for producing a fuel cell member according to claim 7, comprising the steps of: a coating step of coating the adhesive composition for a fuel cell sealing member onto the substrate; a judgment step of judging whether the coating state is good or bad based on the color of the applied adhesive composition; an adhesion step of disposing the uncrosslinked rubber composition on the surface of the substrate to which the adhesive composition has been applied, to form a laminate, and then heating and pressurizing the laminate to crosslink the rubber composition to form the sealing member and adhere the sealing member to the substrate; 2. A method for producing a fuel cell member comprising the steps of:
Citation Information
Patent Citations
Manufacturing method of fuel cell seal body, and rubber gasket for fuel cell used therein
JP2017183198A
Composite
JP2018059630A
Multilayer body
WO2022208926A1